2015
DOI: 10.1159/000381667
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intracranial Hypotension Manifesting as a Unilateral Subdural Hematoma with a Marked Midline Shift

Abstract: Spontaneous intracranial hypotension (SIH) is a syndrome in which hypovolemia of the cerebrospinal fluid (CSF) results in various symptoms. Although its prognosis is usually benign, cases with a rapid neurologic deterioration resulting in an altered mental status have been reported. One of the characteristic radiographic findings in such cases is the presence of bilateral accumulation of subdural fluid (hematoma/hygroma). When SIH-related subdural hematoma is present only unilaterally with a concomitant midlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…In contrast to SMRM, FST2WI is a time-saving and costeffective technique that is useful for revealing various disorders including fluid collections more clearly than other techniques, and is recommended as one of the minimum required sequences. 13,14 As SIH has confounding symptoms including initial low back pain and lumbosacral radiculopathy, 15,16 that might lead clinicians to perform a SMRI examination, it is important to understand imaging findings of routine SMRI techniques including the "Dinosaur tail sign" on sagittal FST2WI. The spinal epidural space lies between the dura mater and the periosteal and ligamentous lining of the vertebral canal.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to SMRM, FST2WI is a time-saving and costeffective technique that is useful for revealing various disorders including fluid collections more clearly than other techniques, and is recommended as one of the minimum required sequences. 13,14 As SIH has confounding symptoms including initial low back pain and lumbosacral radiculopathy, 15,16 that might lead clinicians to perform a SMRI examination, it is important to understand imaging findings of routine SMRI techniques including the "Dinosaur tail sign" on sagittal FST2WI. The spinal epidural space lies between the dura mater and the periosteal and ligamentous lining of the vertebral canal.…”
Section: Discussionmentioning
confidence: 99%
“…SIH needs to be differentiated from the pathophysiologically similar post-lumbar puncture headache, as well as orthostatic headache due to postoperative CSF leakage or shunt over-drainage where there is an obvious trigger. 12 The estimated incidence of SIH is 5 per 100,000 inhabitants, 10 though the real figure might be significantly higher. Women are twice as likely to be affected than men.…”
Section: Discussionmentioning
confidence: 98%
“…SIH needs to be differentiated from the pathophysiologically similar post-lumbar puncture headache, as well as orthostatic headache due to postoperative CSF leakage or shunt over-drainage where there is an obvious trigger. 12…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IC can be the underlying cause of SDH. [ 9 10 11 12 13 14 ] Inadvertent hematoma evacuation may not only be ineffective but also be harmful in such circumstances because further decrease in the intracranial pressure after hematoma evacuation may pull cortical bridging veins downward, resulting in venous wall laceration and acute SDH. [ 9 10 11 12 13 14 ] Interestingly, those cases have manifested almost invariably as chronic SDH from the beginning.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 10 11 12 13 14 ] Inadvertent hematoma evacuation may not only be ineffective but also be harmful in such circumstances because further decrease in the intracranial pressure after hematoma evacuation may pull cortical bridging veins downward, resulting in venous wall laceration and acute SDH. [ 9 10 11 12 13 14 ] Interestingly, those cases have manifested almost invariably as chronic SDH from the beginning. [ 9 10 11 12 13 14 ] Spinal CSF leakage as the cause of conversion to subacute symptomatic SDH, as shown in the present case, has never been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%